Characterization and modeling of forged Ti-6Al-4V Titanium alloy with microstructural considerations during quenching process. (July 2018) - Julien, R.; Velay, V.; Vidal, V.; Dahan, Y.; Forestier, R.; Rézaï-Aria, F.
Highlights: Mechanical tests with prior in-situ heat treatment ( α + β and β -heat-treated alloy). Phase transformation depends on cooling rates influencing the strain–stress response. Model implementation able to predict the behavior for a given phase proportion. Description of the yield point (modified Yoshida model) observed at high temperature Model extended to the behavior prediction of a β -treated Ti-6Al-4V alloy. Graphical abstract: Abstract: The present investigation proposes an experimental device able to assess the thermo-mechanical behavior of Ti-6Al-4V Titanium alloy throughout the die-forging operation. Constitutive equations are developed to assess the influence of the process (die-forging temperature, cooling rate) and the microstructure parameters on the mechanical response of the alloy. For this purpose, a non-unified behavior model formulation is implemented, which defines two main mechanisms related to α and β phases and allows the prediction of hardening, strain rate sensitivity and temperature, combined with the phase evolution that is dependent on the cooling conditions and which can greatly affect the mechanical behavior. This identification strategy is then applied for die-forging temperatures below the β -transus temperature, which requires microstructural information provided by SEM (Scanning Electron Microscopy) observations and image analysis. Finally, the approach is extended to die-forging temperatures above the β -transus temperature.